Ecophysiology of Ruditapes decussatus - Sobral, Maria Paula de Oliveira (2008)
The physiological responses of the clam R. decussatus from the Ria Formosa, southern Portugal, were examined in relation to normoxia, hypoxia (11, 6, 3 and 1.2 kPa) and anoxia; acute elevation of temperature (at 20, 27 and 32 °C), and its effect on the resistance to air exposure (at 20, 28 and 35 °C); current velocity (0.6, 3, 8 17, 24 and 36 cm. s-1) and turbidity (10, 100 and 300 mg. l-1 dry weight of particulate matter), and the efficiency of this species in retaining particles of different size (at 10 and 100 mg. l-1); and to copper contamination considering both short-term acute exposure to high levels (0.1-10 mg Cu. l-1) and chronic environmental levels (0.01 mg Cu. l-1). Clearance rates, respiration rates, absorption efficiency and excretion rates were assessed through the physiological energetics in terms of the energy budget and scope for growth (SFG). Stress independent respiration rates (R) and clearance rates (CR) were observed in relation to hypoxia down to 12 kPa and 6 kPa, respectively. Anoxic rates were 3.6 % of normoxic rates. Scope for growth was greatly reduced under extreme hypoxia (14 % of SFG in normoxia). Respiration rate was temperature independent in the range 20-32 °C but the decline in clearance rate resulted in negative SFG at 32 °C. Gaping during air exposure and the maintenance of faster aerobic metabolism led to 100 % mortality in 20 hours at 35 °C, 4 days at 28 °C and 5 days at 20 °C. Low current velocities (≤ 8 cm. s-1) supported high clearance rates. Shear stresses ≥ 0.9 Pa induced sediment movement and disturbed the feeding processes resulting in decreased clearance rates (at 36 cm. s-1, is 10 % of maximum CR). The observed ability of jetting out depleted water at a different level than the one of the inhalant current results is an important adaptation of clams to the slow currents of sheltered environments. Ingestion at high seston concentrations (> 100 mg. l-1) is controled by reducing the amount filtered, lowering CR (to 30 % of CR at low seston loads) and producing pseudofeces. Observed efficient retention of particles (70-100 %) in the range 3 to 8 μm is beneficial when algal cells are diluted by fine silt particles as it is likely to occur in the clams natural environment. R. decussatus in the short term escaped the exposure to copper by valve closure and therefore acute tests are not applicable to adult clams of this species. At environmental levels chronic exposure to copper did not induce lethal effects during the exposure period (20 days), but scope for growth was reduced to c. 30 %, indicating sustained impairment of physiological functions. The sensitivity of the physiological energetics and the integrated scope for growth measurement in assessing stress effects caused by natural environmental factors was highlighted.